Nurses’ Perception of Patient Safety Culture in the Hospital Accreditation Era: A Literature Review - Puspita Andri, L; Soewondo, P (KnE Life Sciences, 2018)
Hospital accreditation is one of main requirements for health services that is used to improve quality assurance and patient safety. Nurses as the largest number of healthcare professionals and front line of hospital services in community have a big role in determining healthcare quality. Health services are always associated with medical action to human. Patient safety is one of the important points in conducting health services in hospital and also a part of Hospital Accreditation. Patient safety culture should be the attention for the nurses because it is the responsibility of the profession. The purpose of this study was to explore the factors that influence the nurse’s perception of patient safety in the era of hospital accreditation and to review the impact to the quality of health services in hospitals. Methods: Using a literature review, the authors determined inclusion and exclusion criteria, and then performed searches on electronic databases such as ProQuest, EBSCO Host and SAGE Journal. Full-text articles were assessed for eligibility (n = 32). Inclusion and exclusion criteria were set up based on the aim of the study with the publication years being between 2012 and 2017, and finally there were seven articles meeting all the criteria (n =7). As a result of this review, in Saudi Arabia, hospital accreditation increased the nurse’s perception of patient safety. Moreover, in China and Korea, it was seen that the perception of nurses of patient safety decreases the medication errors rate; in Korea, the highest level of perception is on the dimension of managing safety risks. In addition, in Turkey, the perception of nurses of patient safety is very good. It is concluded that the increased knowledge and perception of nurses about patient safety culture has correlation with the hospital accreditation era and gave some input to improve the quality of hospital services. Training, level education and clinical experiment are essentials factors affecting nurse’s perception of patient safety culture. Keywords: nurse’s perception, patient safety culture, hospital accreditation, quality improvement, quality measurement